Influence of dietary linoleic acid inclusion on fatty acid composition in barrows and gilts and its relationship to fat accumulation - Deysi Guevara-Freire; Rosa M. Escudero; Luis Calvo; Ana I. Rodriguez; Raquel Reina; José Ignacio Morales; Álvaro Olivares; Clemente López-Bote (Meat Science, 2026)

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

Development of a biotechnological process for the production of recombinant canine interferon-alpha using the baculovirus-insect cell and larvae system - Maria S. Rodriguez; Ignacio Smith; Marcela S. Villaverde; Joaquin M. Birenbaum; Joaquin Poodts; Federico J. Wolman; Alexandra M. Targovnik; Maria V. Miranda (Biotechnology Letters, 2025)

Optimizing forest planning: Balancing timber production and carbon sequestration through a multi-objective disjunctive formulation - Frank Piedra-Jimenez; Diego Broz; Juan M. Novas; Ignacio E. Grossmann; Maria Analia Rodriguez (Forest Policy and Economics, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Crop nitrogen status and yield formation: A cross-species comparison for maize, rice, and wheat field crops - Ignacio M. Rodriguez; Josefina Lacasa; Gilles Lemaire; Ben Zhao; Syed Tahir Ata-Ul-Karim; Ignacio A. Ciampitti (Field Crops Research, 2024)

Sunflower yield gaps and their causes in Argentina - Ignacio M. Rodriguez; Antonio J. Hall; Juan P. Monzon; Jorge L. Mercau; Sofia Gayo; Monica Lopez Pereira; Anibal Cerrudo; Hernán A. Urcola; Carolina B. Troglia; Sebastián Zuil; María Paolini; Gustavo Martini; et al. (Field Crops Research, 2024)

Revisiting the relationship between nitrogen nutrition index and yield across major species - Ignacio M. Rodriguez; Josefina Lacasa; Emmanuela van Versendaal; Gilles Lemaire; Gilles Belanger; Guillaume Jégo; Patricio G. Sandaña; Rogério P. Soratto; Ivica Djalovic; Syed Tahir Ata-Ul-Karim; Nahuel I. Reussi Calvo; Claudia M. Giletto; et al. (European Journal of Agronomy, 2024)

Cu(II)-acylhydrazone complex, a potent and selective antitumor agent against human osteosarcoma: Mechanism of action studies over in vitro and in vivo models - Lucia M. Balsa; Luisina M. Solernó; Maria R. Rodriguez; Beatriz S. Parajón-Costa; Ana C. Gonzalez-Baró; Daniel F. Alonso; Juan Garona; Ignacio E. León (Chemico-Biological Interactions, 2023)

Fine-tuning the CROPGRO-Sunflower model and its application to the quantification of crop responses to environmental and management variables - Ignacio M. Rodriguez; Jorge L. Mercau; Pablo A. Cipriotti; Antonio J. Hall; Juan P. Monzon (Field Crops Research, 2023)

A novel equation that incorporates the linear and hyperbolic nature of the force–velocity relationship in lower and upper limb exercises - Julian Alcazar; Fernando Pareja-Blanco; Carlos Rodriguez-Lopez; Hector Gutierrez-Reguero; Juan Sanchez-Valdepeñas; Pedro J. Cornejo-Daza; Ignacio Ara; Luis M. Alegre (European Journal of Applied Physiology, 2022)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

CIGB-300, a novel proapoptotic peptide that impairs the CK2 phosphorylation and exhibits anticancer properties both in vitro and in vivo - Silvio E. Perea; Osvaldo Reyes; Idania Baladron; Yasser Perera; Hernán Farina; Jeovanis Gil; Arielis Rodriguez; Dania Bacardi; Jose L. Marcelo; Karelia Cosme; Marisol Cruz; Carmen Valenzuela; et al. (Molecular and Cellular Biochemistry, 2008)

Sex Specificity in Methadone Analgesia in the Rat: A Population Pharmacokinetic and Pharmacodynamic Approach - Monica Rodriguez; M. Angeles Carlos; Ignacio Ortega; Elena Suarez; Rosario Calvo; John C. Lukas (Pharmaceutical Research, 2002)